Voegelin's Noetic Differentiation: Religious Implications - Carmody, John Tully (Horizons, 1981)
For the past sixty years Eric Voegelin has probed the foundations of order and history. After explaining how Voegelin understands "order" and where he places the historical leaps in being that best disclose it, we fix our sights on the noetic differentiation of consciousness—the clarification of human reason launched by classical Greek philosophy. In Part One we expose Voegelin's view of noetic differentiation, beginning with his version of the classical discoveries by Plato and Aristotle. Next we trace the decline that came with the stoics and religion. Finally we conclude with the reality of differentiated reason and what it opens upon. In Part Two we apply this exposition to religion, pursuing the implications of Voegelin's noetic differentiation. The application takes us first to the eros for the divine ground that Voegelin's noesis manifests and the various ways that this eros shows itself in the different religious traditions. Second, the application shows the relevance of noetic differentiation for liberation theology and the theology of revelation.